2017
DOI: 10.7759/cureus.1418
|View full text |Cite
|
Sign up to set email alerts
|

Demographics of Head and Neck Cancer Patients: A Single Institution Experience

Abstract: IntroductionHead and neck cancer (HNC) comprises a diverse group of oncological entities, originating from various tissue types and organ localizations, situated in the topographical regions of the head and neck (H&N). This single institution retrospective study was aimed at establishing the HNC patient demographics and categorizing the individual incidence of H&N malignancies, regarding their organ of origin and main histopathological type.Materials and methodsAll histologically verified cases of HNC from a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…At the current stage, the clinical significance of low dose bath or integral dose in proton therapy is not well known yet, such concerns of radiation-induced secondary malignancy may limit the usage of proton arc technique in pediatric patients' treatment. Based on this study, we are able to conclude that the significant dosimetric advantage of SPArc therapy is to offer a better dose conformity and a better sparing the high or median-dose volume which is critical to the disease sites where the OARs adjunct to the target volume such as HNC where the average age is between 50 and 70 years old [42]. Such a feature could allow proton beam therapy to reduce acute radiation toxicity furthermore.…”
Section: Discussionmentioning
confidence: 75%
“…At the current stage, the clinical significance of low dose bath or integral dose in proton therapy is not well known yet, such concerns of radiation-induced secondary malignancy may limit the usage of proton arc technique in pediatric patients' treatment. Based on this study, we are able to conclude that the significant dosimetric advantage of SPArc therapy is to offer a better dose conformity and a better sparing the high or median-dose volume which is critical to the disease sites where the OARs adjunct to the target volume such as HNC where the average age is between 50 and 70 years old [42]. Such a feature could allow proton beam therapy to reduce acute radiation toxicity furthermore.…”
Section: Discussionmentioning
confidence: 75%
“…This was in accordance with the result of other studies. 11 The most histopathological findings in our study were moderate differentiation (47.8%), whereas carcinoma in situ is the least histopathological finding. This contrasts with the results of a study conducted in other places in Indonesia, that most of the HNSCC patients came with a high differentiation grade or in bad differentiation), 14 or in opposite with the result in the National Referral Cancer Hospital 13 , that the most differentiation from HNSCC patients admitted in the hospital is the good differentiation.…”
Section: Discussionmentioning
confidence: 47%
“…This is followed by adenocarcinoma and lymphoma. The main histopathological groups include squamous cell carcinoma 76.74% and adenocarcinoma 6.14% in the study conducted by George S Stoyanov et al 3 Similarly, the study conducted by Mohammad Shadab Alam et al found squamous cell carcinoma to be the most common Head and Neck carcinoma (97% cases). 8 While analysing the risk factors associated with Head and Neck carcinoma, we found that smoking and chewing together was the most common behavioural risk factor.…”
Section: Risk Factorsmentioning
confidence: 83%
“…Male to female ratio is 2.21: 1. Male to female ratio of the registered HNC cases was 3.24:1 in the study conducted by George S Stoyanov et al 3 However, the study conducted by Mohammad Shadab Alam et al found the male to female ratio to be 16:1. 8 Our study concluded that squamous cell carcinoma is the most common histological type of carcinoma (87.78%).…”
Section: Risk Factorsmentioning
confidence: 90%
See 1 more Smart Citation